Mitochondrial genetic variation in bowhead whales in the western Arctic - Taylor , B. L.; LeDuc , R. G.; Martien , K. K.; Morin , P. A.; Hedrick , N.; Robertson , K. M.; Mugue, N. S.; Borodin , R. G.; Zelenina , D. A.; Litovka , D.; George , J. C. (J. Cetacean Res. Manage., 2023)
Bowhead whales in the Western Arctic are managed as a single stock by the International Whaling Commission (IWC). In response to recent concerns about the potential existence of multiple stocks in the region, we examined genetic variation in the mitochondrial control region among various spatial, temporal and age-related strata. Sequences from 382 samples were used in the comparisons. No significant differences were detected in spatial comparisons or in temporal comparisons along Alaska’s North Slope. However the cc2 analysis showed evidence of genetic heterogeneity between some of the age cohorts, specifically between animals born prior to 1918 (n=8) and those born after 1979 (n=34) (p=0.030), between those born 1918-1949 (n=13) and those born after 1979 (p=0.050), and between the two aforementioned older cohorts and those born after 1979 (p=0.009). There was also a significant Fst difference between autumn (n=13) and spring (n=11) whales from St. Lawrence Island (p=0.049). The age data were insufficient to determine if this seasonal difference was due in part to the difference between age cohorts.